On the Uniqueness of Traveling Forced Curvature Fronts in a Fibered Medium (Journal of Mathematical Study, 2019)
We investigate traveling fronts, including pulsating ones, of a forced curvature flow in a plane fibered medium. The main topic of this note is a uniqueness issueof such traveling fronts. In addition to line-shaped profiles, we also consider travelingfronts in the form of V-shaped parabolas.